Relación entre depresión y síndrome de burnout en adultos: una revisión aplicada - Marin Reyes, Hugo (2023)
Depression has a significant prevalence among mental disorders. Likewise, burnout is a syndrome caused by work stress, which is also a trend in the field of research. Depression has a significant prevalence among mental disorders. Likewise, burnout is a syndrome caused by work stress, which is also a trend in the field of research. The aim of this paper is to review the empirical evidence of previous work associating these two variables in adulthood. An applied review was carried out according to the PRISMA model. The databases consulted were: Scopus, Web of Science, Scielo, EBSCO, PubMed and Proquest. Through the use of inclusion and exclusion criteria, ten articles were selected for subsequent analysis. It was found that, in all the investigations, depression and burnout were positively correlated. In mayority studies, depression was positively correlated with some dimensions of bunout like exhaustion and despersonalization. Self realisation was negativey correlated with depression symptomps. In conclusion, the greater the burnout, the greater the depressive symptomatology.